FENOMENOLOGI E-LEADERSHIP DALAM KONSTRUKSI TATA KELOLA MUTU: KONTEKS KEUNGGULAN SISTEM INFORMASI - Naufal Ilyas Fauzan; Ubaid Al Faruq; Ruknan (STKIP Subang, 2026)
The era of digital disruption demands higher education, especially Islamic educational institutions, to reform their governance architecture through technology integration and adaptive leadership. This study aims to explore in depth the phenomenology of e-leadership in the construction of quality governance based on information system excellence at IAI Al-Hidayah Bogor. Employing a qualitative method with an Interpretative Phenomenological Analysis (IPA) approach, this research delves into the subjective lived experiences of leaders in interpreting and managing the institution's digital transformation. The results reveal that e-leadership is perceived not merely as the adoption of technical tools but as a manifestation of prophetic values (Sidiq, Amanah, Fathonah, Tabligh) transformed into instruments of digital transparency and accountability. The optimization of integrated information systems (e-Campuz, SISTER, and Neo Feeder) has triggered a shift in the decision-making paradigm from intuitive-subjective patterns to Data-Driven Decision Making (DDDM) through a data-to-wisdom transformation mechanism. Furthermore, the resulting quality governance construction forms an organizational